PENGARUH CONTENT MARKETING MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI KONSUMEN PADA USAHA YOURGOOD - Adzhani, Marsha Edina; Pujianto, Totok; Syahmurman, Faizal (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Utilization of information technology that is increasingly accessible is one of the strategies for entrepreneurs to market their products. YourGood business is one of the Small and Medium Enterprises (SMEs) by presenting smoothies yogurt products and using social media as a marketing medium, one of which is content marketing through Instagram social media as a marketing strategy, content marketing is one of the most important marketing strategies currently being used by YourGood business. The purpose of this study is to test as an illustration how the role or influence of the contribution of content marketing through Instagram social media run by YourGood business on consumer buying interest, this research is included in the type of explanatory research method with a quantitative approach and using non-probability sampling with purposive sampling with a total of 100 respondents using a linear time function to determine the number of samples. Researchers used normality test analysis, t test, F test and multiple linear regression using Microsoft Excel 2019 software. The results stated that there was a correlation between marketing Instagram social media content and the buying interest of YourGood business consumers by 62.6%. Then the variable that has the greatest value is the persuasion variable of 47%. So that the content marketing strategy that can be carried out by YourGood business is to present content with product quality information and build trust in consumers and be carried out consistently and attractively so that the content marketing strategy will be able to increase consumer buying interest.Keywords: Content Marketing, Purchase Intention, Digital Marketing, Instagram.